Statistical Modeling for Sentiment Classification: A Review - Pal, Varsha; Varkale, Akshay (International Journal of Computer Sciences and Engineering, 2020)
Sentiment classification is the process of using NLP, statistics, or machine learning methods to extract, identify, or otherwise characterize the sentiment content of a text unit. Based on a sample of tweets, how are people responding to this ad campaign/product release/news item? There are several application of opinion mining such as on business intelligence, Politics/political science, Law/policy making, Sociology, Psychology etc. By use of digital platform administration can collect response from consumer and by means of applying opinion mining technique a useful information from user collected data. In this paper we have given a brief review over different work done in the field of sentiment classification and given tabular comparison among different opinion classification technique based on accuracy.